Intermediate Production of Skin and Leather Goods and Intra-Regional Trade: The Case of Mali in the ECOWAS Region - Bassole, Ibrahim; Maiga, Ibrahim (Balai Publikasi Indonesia, 2025)
Our article aims to promote the link between intermediate production of skin and leather goods and intra-regional trade in Mali within the ECOWAS region. Indeed, it first examines the importance of large-scale industrial processing units with approximately 76% of total tanning of skins produced in Mali (Table 3). Then the article shows that the intra-regional trade flows of skin and leather from Mali illustrate the importance of size in the intra-regional trade relationship (Figure 4). Finally, the article identified the profile of the actors operating in ECOWAS intra-regional trade in intermediate production of skin and leather goods. This mainly concerns the profile of suppliers and demanders in intermediate production activities of skin and leather goods. On the other hand, the economic literature remains poorly documented on the subject, especially very specifically for our region. Among the studies that are interested in our subject, we can cite: that of Bassolé (2022) and Dabié Désiré Axel NASSA (2005). Regarding the methodology used, it is mainly based on the Bassolé thesis (2022), carried out in two stages on the profile of the actors operating in ECOWAS intra-regional trade.